Secrets & mysteries of Christopher Columbus - Perry, Paul, 1950-; Goyette, Charles; Sakkara Productions; Soundview Media Partners ([Paradise Valley, Ariz. ] : Sakkara Productions, 2018)
Was Christopher Columbus born in Genoa, Italy? An unlikely collection of experts from European royalty, DNA science, university scholars, even Columbus's own living family so he definitely was not. This ground breaking documentary follows a trail of proof to show the Christopher Columbus might have been much more than we know.
Originally released as a motion picture in 2018.
Narrator: Charles Goyette.
Director of cinematography, Marlin Darrah ; cinematographers, Reed Perry, Carlos Casimiro, Michael Sly ; editor, Sam Worseldine.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed January 30, 2020)
Keywords: Columbus, Christopher; Explorers -- America -- Biography; Explorers -- Spain -- Biography; Documentary films; Biographical films; Nonfiction films; Internet videos; Streaming video